The usefulness of the T1DDS simulator in the context of multi-day type 1 diabetes therapy - Nowicki, Tomasz (Journal of Computer Sciences Institute, 2024)
The motivation behind the research described in this article was to explore the possibility of using the T1DDS simulator in the context of type 1 diabetes therapy lasting longer than one day. The T1DDS simulator has so far been used within a one-day scope and in this form was employed as the computational engine in the educational application T1DCoach. A natural step in seeking further applications of the simulator is the attempt to use it to support real therapy. The article presents the capabilities of the simulator in its original form regarding therapeutic areas of application.